Aiaa Aviation 2021 Forum 2021
DOI: 10.2514/6.2021-2147
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Perforations for the Reduction of Turbulence-Aerofoil Interaction Noise: Part II - Theoretical Investigation

Abstract: This paper presents a theoretical study of introducing a single gap or slot downstream of the leading edge of a thin rigid plate on aeroacoustic scattering. This is investigated as an elementary model for understanding the effect of downstream perforations on gust-aerofoil interaction noise. Across the slot it is supposed there is zero pressure jump, and a wake is shed from the upstream slot edge such that an unsteady Kutta condition is satisfied. The resulting mixed boundary value problem is reformulated as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Priddin et al [20] have also explored the noise reduction mechanism of a flat plate upstream of a semi-infinite leading edge subject to a harmonic vortical gust. Predictions of the noise reduction spectra obtained analytically from solutions of the wave equation with appropriate boundary conditions imposed 390 were found to capture the envelope of the experimental noise reduction spectra, but not the distinctive peaks and dips.…”
Section: Sensitivity Of Noise Reductions To the Chordwise-length L Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…Priddin et al [20] have also explored the noise reduction mechanism of a flat plate upstream of a semi-infinite leading edge subject to a harmonic vortical gust. Predictions of the noise reduction spectra obtained analytically from solutions of the wave equation with appropriate boundary conditions imposed 390 were found to capture the envelope of the experimental noise reduction spectra, but not the distinctive peaks and dips.…”
Section: Sensitivity Of Noise Reductions To the Chordwise-length L Of...mentioning
confidence: 99%
“…However, the mechanisms proposed in [16,20,21] individually cannot explain the shape of the noise reduction spectra, which comprises a number of distinct peaks at f l d /U c = n, superimposed on a broad 'envelope' that decays with increasing frequency. The peaks are particularly pronounced in the case 400 of the tandem flat plates in Fig.…”
Section: Sensitivity Of Noise Reductions To the Chordwise-length L Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, novel concepts for designing porous airfoils based on nonuniform distributions of porosity have been proposed. Paruchuri et al [19], Palleja-Cabre et al [20], and Priddin et al [21] investigated the leading-edge noise reduction achieved by flat plates with different extents of porous inserts and showed that a single row of holes located downstream of the stagnation point results in significant mitigation at low frequencies without increasing the noise emissions at high frequencies. Ayton et al [22] found that smoothly varying chordwise porosity on a perforated flat plate can be beneficial for reducing trailing-edge noise thanks to the more significant destructive interference of the back-scattered field generated by the impermeable leading edge [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Ocker et al [33] considered a wide range of porous structures for permeable leading edge airfoils to systematically study the effect of the porous structure on turbulence interaction noise and fan noise. Palleja-Cabre et al [36] and Priddin et al [38] experimentally and analytically studied a flat plate in a turbulent stream in a two part study. The flat plate had perforations downstream of the leading edge and demonstrated a noise reduction which is likely attributed to the airfoil acting as though it has a shorter chord.…”
Section: Introductionmentioning
confidence: 99%